Consolidant treatment of Irish sandstone - Kissane, Paul (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2007)
The objective of this study was to assess the efficiency of consolidant treatments in improving the durability of Irish sandstones. Samples of sandstones relevant to national monuments were characterised, artificially weathered and treated with modified alkoxysilane consolidants. The mass structure, moisture transfer and mechanical properties of unweathered, weathered and treated samples were compared in order to estimate the variation in properties due to weathering and treatment. These variations were used to evaluate the suitability of the treatments. Further weathering tests were also carried out in order to compare the durability of the treated and untreated samples. Treated samples lost considerably less material than untreated ones.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin